Risk factors for infectious keratitis - a literature review - Sereda, Dominika; Nieścior, Hubert; Metelska, Aleksandra; Metelski, Jakub; Szwed, Monika (Journal of Education, Health and Sport, 2022)
Introduction and purpose Infectious keratitis represents the leading cause of corneal blindness worldwide, particularly in developing countries. Both risk factors and etiological patterns vary between economically developed and developing regions, with bacterial predominance in the former and fungal predominance in the latter. This review aims to provide an updated overview of the risk factors in relation to infectious keratitis. Description of the state of knowledge Infectious keratitis is a painful and potentially vision-threatening ophthalmic condition characterized by decreased vision, photophobia and eye redness. In severe cases, it may require hospital admission for intensive medical treatment or surgical interventions. It can be caused by a wide array of organisms, including bacteria, fungi, viruses, parasites or polymicrobial infection. The most commonly observed predisposing factors for infectious keratitis include contact lens wear, trauma, ocular surface diseases, post-corneal surgery and systemic or local immunosuppression. Manual workers in construction or agricultural industry, exposed to vegetative matter, organic materials and animal products are particularly at risk. Higher rate of incidence is also observed in regions with poor environmental and personal hygiene, low level of education, poor access to sanitation and healthcare facility. Summary Persistent prevalence of infectious keratitis in both developed and developing countries makes it a serious medical problem. Prevention, proper diagnosis and effective treatment are crucial for positive visual outcome.